Unnecessarily tied to the professor: the outcomes of systematic correction on the Dunning-Kruger effect in an educational context - Vílchez, Jose Luis (Transformación, 2024)
Objective: The Dunning-Kruger effect is the cognitive bias by which incompetent individuals overestimate their own abilities or underestimate others’. This paper aims at describing the effect of the professor’s feedback on individual self-assessment of their individual’s potentials. Methods: The study is a quantitative, quasi-experimental and descriptive research. First, the cognitive bias in the self-evaluation-real performance of bad students was compared to good students (first VI), "Neurophysiology", third semester class. Then, after receiving teacher’s feedback, participants were given a second test for assessing a second variable. Results: The findings point out that there is a Dunning-Kruger effect showing a significantly greater cognitive bias in the self-evaluation between bad students and good students. For the second test (after the systematic teacher’s feedback of individual errors, this effect between disappears, both in bad students and good students. Furthermore, there is a significant decrease in this cognitive self-assessment bias in the group of poor students between the first test and second test. Conclusion: This study shows that there is a Dunning-Kruger effect in the educational context and a dependency on the feedback given by the professor, due to the student’s inability to be aware of their own knowledge (which prevents their progress).